(untitled) (Jurnal Sistem Informasi Akuntansi, 2023)
Over time, the use of information technology continues to increase both among ordinary people and in institutions. KPRI-Tamansari really needs an information system that supports good and good service to its members. Therefore, the author tries to realize the final project about the Tamansari KPRI Savings and Loans System which has not been computerized. KPRI-Tamansari is a branch of the Savings and Loans Cooperative run by a group of elementary school teachers and UPT staff, as well as civil servants and volunteers, in Tamansari District, Bogor Regency. Currently KPRI Tamansari uses a recording system in books and data storage using the Microsoft Excel application, so there is a possibility of errors when calculating or storing data. Therefore, KPRI-Tamansari requires a computerized system that allows recording of all types of savings and loan transactions and generating reports. Computerized systems are expected to work more efficiently and effectively than traditional systems